Pressure Balance Cross-Calibration Method Using a Pressure Transducer as Transfer Standard. Issue 1 (2nd January 2016) - Scherschligt, Julia; Olson, Douglas A.; Driver, R. Gregory; Yang, Yuanchao
Abstract: Piston gauges or pressure balances are widely used to realize the SI unit of pressure, the pascal, and to calibrate pressure sensing devices. However, their calibration is time consuming and requires a lot of technical expertise. In this article, we propose an alternate method of performing a piston gauge cross calibration that incorporates a pressure transducer as an immediate in-situ transfer standard. For a sufficiently linear transducer, the requirement to exactly balance the weights on the two pressure gauges under consideration is greatly relaxed. Our results indicate that this method can be employed without a significant increase in measurement uncertainty. Indeed, in the test case explored here, our results agreed with the traditional method within standard uncertainty, which was less than 6 parts per million.